Description and Outcomes of an Innovative Concurrent Hospice-Dialysis Program. Issue 10 (October 2022) - Ernecoff, Natalie C.; Bursic, Alexandra E.; Motter, Erica M.; Lagnese, Keith; Taylor, Robert; Schell, Jane O.
Significance Statement: Patients with ESKD access hospice care only about half as often as patients in the general Medicare population. A novel Concurrent Hospice and Dialysis Program aims to improve hospice access for patients with ESKD by offering palliative dialysis concurrently with hospice care. This paper describes the structure of the Program and presents a quantitative description of enrollees. Our 3-year experience with the Program demonstrated that patients had a median hospice length of stay longer than that found in previous reports and provides evidence to support future work to test the effectiveness of such clinical programs. Abstract : Background: Compared with the general Medicare population, patients with ESKD have worse quality metrics for end-of-life care, including a higher percentage experiencing hospitalizations and in-hospital deaths and a lower percentage referred to hospice. We developed a Concurrent Hospice and Dialysis Program in which patients may receive palliative dialysis alongside hospice services. The Program aims to improve access to quality end-of-life care and, ultimately, improve the experiences of patients, caregivers, and clinicians. Objectives: We sought to describe ( 1 ) the Program and ( 2 ) enrollment and utilization characteristics of Program participants. Methods: We conducted a quantitative description of demographics, patient characteristics, and utilization of Program enrollees. Results: Of 43 total enrollees, 44% received at least one dialysis treatment, whereas 56% received no dialysis. The median (range) hospice length of stay was 9 (1–76) days for all participants and 13 (4–76) days for those who received at least one dialysis treatment. The average number of dialysis treatments was 3.5 (range 1–9) for hemodialysis and 19.2 (range 3–65) for peritoneal dialysis. Sixty-five percent of enrollees died at home, 23% in inpatient hospice, and 12% in a nursing facility; no patients died in the hospital. Conclusions: Our 3-year experience with the Program demonstrated that enrollees had a longer median hospice stay than the previously reported 5-day median for patients with ESKD. Most patients received no further dialysis treatments despite the option to continue dialysis. Our experience provides evidence to support future work testing the effectiveness of such clinical programs to improve patient and utilization outcomes.